2021
DOI: 10.1186/s12889-021-10820-x
|View full text |Cite
|
Sign up to set email alerts
|

Domestic violence in Mozambique: from policy to practice

Abstract: Background To reduce the impact of domestic violence (DV), Mozambican governmental and non-governmental entities are making efforts to strengthen the legislative framework and to improve the accessibility of care services for survivors of violence. Despite this remarkable commitment, the translation of policies and legislation into actions remains a considerable challenge. Therefore, this paper aims to identify gaps in the implementation of existing national policies and laws for DV in the serv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 56 publications
0
1
0
Order By: Relevance
“…4). Additionally, a recent study by Jethá et al (2021) revealed the absence of a specific national DV database in the country under examination. Establishing clear laws and promoting awareness of social services are essential in combating domestic violence within families and society as a whole.…”
Section: Discussion: National Definitions and Multidisciplinary Effortsmentioning
confidence: 99%
“…4). Additionally, a recent study by Jethá et al (2021) revealed the absence of a specific national DV database in the country under examination. Establishing clear laws and promoting awareness of social services are essential in combating domestic violence within families and society as a whole.…”
Section: Discussion: National Definitions and Multidisciplinary Effortsmentioning
confidence: 99%
“…While the global prevalence of IPV is estimated at about 30%, it is particularly prevalent in sub-Saharan Africa, where the overall prevalence is 36%. Compared to the rest of the world, women in sub-Saharan Africa are more affected by domestic violence than men (Jethá et al, 2021). In some southern African countries, levels of sexual abuse of women are even higher (Ahinkorah et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Generally, IPV disproportionately affects more women than men. Worldwide, one in three women has been physically and/or sexually abused by her intimate partner or family members at some point in her lifetime, compromising their physical, mental, and reproductive health (Jethá et al, 2021). Violence in intimate partner relationships is usually attributed to gender norms that promote male dominance over women and women's acquiescence to male power (Shai et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite numerous intervention efforts over the last decade, the burden of IPV continues to grow (Stöckl et al, 2014). IPV is particularly prevalent in sub-Saharan Africa where the overall prevalence is 36%; compared to the rest of the world, sub-Saharan African women are more affected by domestic violence than men (Jethá et al, 2021), and women are more likely to be injured by intimate partners, suffer from more severe IPV types, and are more likely to fear for their lives than male victims (Fanslow et al, 2023). In Mozambique, for example, 40% of women of reproductive age (15-49 years) reported the experience of physical, sexual or emotional violence perpetrated by an intimate male partner in the last 12 months (Tura and Licoze, 2019).…”
Section: Introductionmentioning
confidence: 99%